Dating systemic financial stress episodes in the EU countries - Thibaut Duprey; Benjamin Klaus; Tuomas A. Peltonen (European Central Bank (ECB), 2015)
This paper introduces a new methodology to date systemic financial stress events in a transparent, objective and reproducible way. The financial cycle is captured by a monthly country-specific financial stress index. Based on a Markov Switching model, high financial stress regimes are identified and a simple algorithm is used to select those episodes of financial stress that are associated with a substantial negative impact on the real economy. By applying this framework to 27 EU countries, the paper is a first attempt to provide a chronology of systemic financial stress episodes in addition to the expert-detected events available so far.
Keywords: C54; G01; G15; 330; Crises Dating; Financial Stress Index; Markov Switching; Systemic Financial Crises